Decline in surface urban heat island intensity in India during heatwaves. (4th April 2019) - Kumar, Rahul; Mishra, Vimal
Abstract: Heatwaves cause human mortality around the world and are projected to rise in the future. Despite the influence of urban heat island (UHI) on heatwaves, the role of UHI on heatwave intensification in urban areas in India remains unrecognized. Here using in situ, satellite observations, and model simulations, we show that urban areas in India do not intensify heatwaves. The frequency of hot-days has significantly (p-value <0.05) increased in urban areas during 1951–2016. The frequency of hot-nights has also increased in the majority of urban areas in India except those located in Indo-Gangetic Plain (IGP). We show that a decline in the frequency of hot-nights (−4.5 ± 1.6 hot-nights) in IGP during 1951–2016 is mainly due to intensive irrigation in the region. We confirm the influence of irrigation on land surface temperature (LST) over IGP using simulations from Community Land Model (CLM4). Our results show that Surface Urban Heat Island (SUHI) intensity in major urban areas in India declines during heatwaves both during the day (−0.3 ± 0.7 °C) and night (−0.3 ± 0.4 °C) from the reference SUHIs. Surrounding non-urban areas (44.5 ± 5.5 °C) are warmer than urban areas (43.7 ± 6.8 °C) during heatwaves due to the absence of vegetation. Our results have implications for policy related to health impacts during heatwaves.